LUNG RADS 1.1 – A Case-Based Review: What’s New? - Guha Roy , S.; Mackey , J.; ,; ,; ,; , (Seram, 2021)
Background Information: National Lung Cancer Screening Trial (NSLT) paved the pathway for routine annual low dose chest computerized tomography (CT) screening for lung cancer in high-risk patients. Since 2014, the American College of Radiology (ACR) laid out the Lung Imaging Reporting and Data System (LUNG-RADS) to standardize reporting and management of CT lung screening. Earlier this year, the ACR published the new LUNG-RADS system, version 1.1. Educational Goals/Teaching Points: In this case-based exhibit we will review imaging features of lung nodules detected on screening CT, how to characterize them based on LUNG-RADS 1.1 and what are the follow-up recommendations. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: Imaging characteristics of lung nodules. Definitely benign vs solid or ground glass nodules. Measurement of lung nodules: highlight on the new version 1.1. Peri-fissural nodule: what’s new? Volumetric assessment of nodules. Recommendations for follow-up of each type of nodules: highlight on the changes in version 1.1. What to include in the report? Summary of the changes in version1.1. Conclusion: Lung cancer screening CT is now routine in any radiology practice. Awareness with LUNG-RADS system and the new amendments are essential for correct diagnosis and follow-up recommendation.